Determinação de Fe, Cu, Mn, Ni, V e Ti em partículas totais em suspensão coletadas em uma área urbana da cidade de Aracaju, Sergipe - Almeida, Tarcísio Silva de (2012)
This study aimed to determine and assess the total concentration of trace elements associated with the total suspended particles (TSP) collected in an urban area of the Aracaju City, Sergipe, Brazil. Forty two samples were collected on glass fiber filters between period August/2009 and September/2010 using a high volume sampler (AGV). The concentration of Fe, Cu, Mn, Ni, V and Ti were determined employing atomic spectrometry techniques in two different work. The first used acid digestion extraction assisted by microwave and analysis by mass spectrometry and optical emission, both inductively coupled plasma (ICP OES and ICP MS). The concentrations of the elements found between <48 and 1620 ± 16 ng.m-3 for Fe; 0.70 ± 0.04 and 322 ± 4 ng.m-3 for Cu;<1,3 and 12.7 ± 6.8 ng.m-3 for Mn; 1.1 ± 0.1 and 16.0 ± 8.4 ng.m-3 for Ni; <15 and 49.3 ± 4.0 ng.m-3 for V and 4,6 ± 0,6 a 129,0 ± 12,5 ng.m-3 for Ti (n=41 samples). The exploratory data analysis results was applied. Principal component analysis (PCA) and hierarchical cluster analysis (HCA) concluded that there are two emitters that contribute to the composition of the PTS that reach the sampling area. Soil resuspension is major contributor in the composition due to correlation between Fe, Mn, Ni and Ti, which are typical elements of the soil. The second emitter, is characteristic of the vehicular traffic. wherein the concentration of Cu, V, SO2 and smoke were likely indicative of action anthropogenic. The enrichment factor calculated for the concentration of the elements identified enrichment for the average concentration of copper found in the urban area, is another indication of anthropogenic inputs. The second study consisted of the Cu and Fe sequential determination in TSP using slurry sampling flame atomic absorption spectrometry and mode fast sequetial (FS-FAAS). The optimization univariate involved the following variables: the concentration of nitric acid used to prepare the slurry, sonication time and the sample mass. The optimized conditions, to about 50 mg of sample were: nitric acid solution 0.5 mol L-1, sonication time of 10 min and a final volume of 25 mL. The calibration curves were obtained using a slurry of a non-filter, the pattern multielement containing Cu and Fe in nitric acid 0.5 mol L-1. This strategy calibration offset the effect observed for the matrix Fe The limit of detection (LOD, 3σ, n = 10) was equal 4 μg.g-1 for Cu and 14 μg.g-1 for Fe , corresponding to 8 ng.m-3 for Cu and 20 ng.m-3 for Fe. The precison was expressed as relative standard deviation (RSD, n = 3) was smaller than 7% for the copper concentration and 8% for iron concentration in the slurries analysis (n=3). The concentrations of both elements determined by the proposed method were compared to concentrations obtained by ICP-MS after acid extraction assisted by microwave and showed no significant differences, applying the t test for a confidence level of 95%. The proposed procedure was simple, fast and reliable suitable for the sequential determination of Cu and Fe in PTS samples by FS-FAAS.